Ambivalence for Cognitivists: A Lesson from Chrysippus?. (21st April 2017) - Wringe, Bill
Abstract: Ambivalence—where we experience two conflicting emotional responses to the same object, person or state of affairs—is sometimes thought to pose a problem for cognitive theories of emotion. Drawing on the ideas of the Stoic Chrysippus, I argue that a cognitivist can account for ambivalence without retreating from the view that emotions involve fully‐fledged evaluative judgments. It is central to the account I offer that emotions involve two kinds of judgment: one about the object of emotion, and one about the subject's response.